Construction and Characterization of an Isogenic slt-ii Deletion Mutant of Enterohemorrhagic Escherichia coli - Gunzer, Florian (American Society for Microbiology, 1998)
Enterohemorrhagic Escherichia coli (EHEC) produces Shiga-like toxins (SLT), potent protein synthesis inhibitors. To further dissect the role of SLT-II in the course of disease, we have constructed E. coli TUV86-2, an isogenic SLT-II-negative mutant of EHEC strain 86-24. The slt-ii gene was inactivated by suicide vector mutagenesis. We also isolated derivatives of strain 86-24 that were cured of the phage carrying the toxin genes.